Take me (I'm yours). - Obrist, Hans Ulrich; Schlieker, Andrea (London : Serpentine Gallery, 1995)
Boltanski, Christian ; Eichhorn, Maria ; Feldmann, Hans-Peter ; Geys, Jef ; Gilbert & George ; Gordon, Douglas ; Hill, Christine ; Höller, Carsten ; Hyber, Fabrice ; Tillmans, Wolfgang ; Weiner, Lawrence ; West, Franz
Take me (I'm yours), Serpentine Gallery, London, 24 March - 30 April 1995 ; Touring to: Castello di Rivara, Turin, 20 May - end June 1995 ; Kunsthalle Nuremberg, 27 July - 17 September 1995
biografie
Engels
kunstcatalogus